Influence of different fat sources on the performance, egg quality, and lipid profile of egg yolks of commercial layers in the second laying cycle - Da Silva Filardi, R. [UNESP]; Junqueira, O. M. [UNESP]; De Laurentiz, A. C. [UNESP]; Casartelli, E. M. [UNESP]; Aparecida Rodrigues, E. [UNESP]; Francelino Araújo, L. (Elsevier, 2005)
This study was designed to evaluate the effects of different fat sources on the performance, egg quality, and lipid profile of the egg yolks of layers in their second production cycle. The fat sources were cottonseed oil, soybean oil, lard, sunflower oil, or canola oil. Experimental diets were fed to postmolt ISA Brown layers at 70 wk of age and the experimental period was 74 to 86 wk of age. The different fat sources did not influence performance or eggshell quality, but lipid profile of the egg yolk changed as a function of dietary fat sources. In general, the best changes, such as lower level of saturated fatty acids, higher levels of α-linolenic acid and DHA, and lower linoleic acid levels, were promoted by the addition of canola oil, but it did not promote enrichment of the eggs with polyunsaturated fatty acids. ©2005 Poultry Science Association, Inc.
Keywords: Fatty acids; Forced molt; Lipid profile; Semi-heavy layers